Natural hazards in Bangladesh : studies in perception, impact, and coping strategies - Islam, Nazrul; University of Dhaka. Disaster Research Training and Management Centre (Dhaka : Disaster Research Training and Management Centre (DRTMC), 2005)
Specially on flood damage and disaster relief in Bangladesh; articles.
Includes bibliographical references.
Keywords: Flood damage -- Bangladesh; Disaster relief -- Bangladesh